Religion, expression and patriotism in Russia : essays on post-Soviet society and the state - Aitamurto, Kaarina; Turoma, Sanna; Vladiv-Glover, Slobodanka (Ibidem Press, 2019)
This volume presents seven case studies that probe into the politics of religion and culture in today's Russia. The contributions highlight the diversity of Russia's religious communities and cultural practices.